2013
DOI: 10.1155/2013/583013
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms and Their Sensitivity Pattern in Septic Arthritis of North Indian Children: A Prospective Study from Tertiary Care Level Hospital

Abstract: Background. Septic arthritis is a true orthopaedic emergency. Important factors determining outcome are rapid diagnosis and timely intervention. Changing trends in microbiological spectrum and emerging drug resistance poses big challenge. Present study evaluates bacterial strains and their sensitivity pattern in septic arthritis of North Indian children. Methods. Fifty children with septic arthritis of any joint were evaluated. Joint was aspirated and 2 cc of aspirated fluid was sent for gram stain and cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…7 Yadav et al found that fluid showed isolates in 72.0% of cases. 10 The most common organism was Staphylococcus aureus (62.0%) followed by Streptococcus pneumonia and Gr. B Streptococcus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Yadav et al found that fluid showed isolates in 72.0% of cases. 10 The most common organism was Staphylococcus aureus (62.0%) followed by Streptococcus pneumonia and Gr. B Streptococcus.…”
Section: Discussionmentioning
confidence: 99%
“…The common consequence was satisfactory in 70.3% of subjects with quick diagnosis and management. 10 Due to the scarcity of signs and symptoms, neonatal septic arthritis frequently goes unrecognized at the establishment with possible sources of overwhelming difficulties counting the expiry of the newborn. Staphylococcus aureus is conveyed to be the common offender of this disorder worldwide, while other organisms isolated in culture comprise Klebsiella pneumonae, group B Streptococci, Escherichia coli, Enterobacter sp., Kingella kingae, and Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid diagnosis and speedy initiation of targeted therapy are necessary to prevent devastating joint consequences and to prevent further systemic spread 13, 14 . Despite advancement in laboratory diagnostic methods and improvement in treatment options, Septic arthritis still results in notable mortality 4, 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, bacteria can be identified through staining and culture of the synovial fluid [ 20 ]. While gram-positive cocci like Staphylococcus aureus are the most common causative organisms, other pathogens can also lead to septic arthritis [ 37 ].…”
Section: Reviewmentioning
confidence: 99%